Technické studie silnice I/23 - obchvat Zakřan - Píštěk, Petr (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Cílem diplomové práce je zpracování technické studie I/23 – obchvat Zakřan. Obec se nachází v Jihomoravském kraji. Obec leží 25km západně od krajského města Brno. Cílem studie je vyhledat vhodnou variantu, která projde jižně od obce Zakřany. Zároveň bylo požadováno vyhnout se zalesněným oblastem. Výsledná varianta, která vzešla z dalších dvou navržených, prochází zemědělským území. Při projekci byl brán ohled na územní plán dotčených katastrů obcí.

The goal of the diploma thesis is prepare a technical study of I/23 – bypass Zakřan. Village is situated in South-moravia region. Village is located 25km western from region city Brno. The goal of the study is find the best variant, which passes southest of the village Zakřany. At the same time it was required to avoid wooded areas. The final variant, which came up from two other draft, passes through agricultural territory. The concideration has been taken to land use plan of villages during a projection.
Technical studies of road I / 23 - bypass Zakřan
Keywords: Technická studie; Zakřany; Obchvat; Extravilán; Komunikace I/23; S9; 5/90; Technical study; Zakřany; bypass; extra region; road I/23; S9; 5/90